Local and systemic therapy may be safely de-escalated in elderly breast cancer patients in China: A retrospective cohort study - Wang, Ji; Fu, Hongtao; Zhong, Zhaoyun; Jiang, Yunshan; Pan, Hong; Sun, Xiaowei; Xu, Weiwei; Tang, Xinyu; Zhou, Wenbin; Wang, Shui (Frontiers in Oncology, 2022)
Background: For elderly patients with breast cancer, the treatment strategy is still controversial. In China, preoperative axillary lymph node needle biopsy is not widely used, resulting in many patients receiving axillary lymph node dissection (ALND) directly. Our study aims to determine whether local and systemic therapy can be safely de-escalated in elderly breast cancer. Methods: Patients aged ≥70 years were retrospectively enrolled from our institution’s medical records between May 2013 and July 2021. Groups were assigned according to local and systemic treatment regimens, and stratified analysis was performed by molecular subtypes. Univariate and multivariate survival analyses were used to compare the effects of different regimens on relapse free survival (RFS). Results: A total of 653 patients were enrolled for preliminary data analysis and 563 patients were screened for survival analysis. The mean follow-up was 19 months (range, 1-82 months). Axillary lymph node metastases were pathologically confirmed in only 2.1% of cN0 cases and up to 97.1% of cN+ cases. In the aspect of breast surgery, RFS showed no significant difference between mastectomy and BCS group (P = 0.3078). As for axillary surgery, patients in ALND group showed significantly better RFS than those in sentinel lymph node biopsy (SLNB) group among pN0 patients (P = 0.0128). Among these cases, the proportion of cN+ in ALND was significantly higher than that in SLNB (6.4%vs 0.4%, P = 0.002), which meant axillary lymph nodes (ALNs) of ALND patients were larger in imaging and more likely to be misdiagnosed as metastatic. With regard to adjuvant therapy, univariate and multivariate analyses showed that RFS in different comprehensive adjuvant regimens were similar especially among hormone receptor (HR)+/ human epidermal growth factor receptor 2 (HER2)- subgroup where patients who did not receive any adjuvant therapy accounted for 15.7% (P＞0.05). Conclusions: It is feasible to reduce some unnecessary local or systemic treatments for elderly breast cancer patients, especially in HR+/HER2- subtype. Multiple patient-related factors should be considered when making treatment plans.